AFLOW‐SYM: platform for the complete, automatic and self‐consistent symmetry analysis of crystals. Issue 3 (3rd May 2018) - Hicks, David; Oses, Corey; Gossett, Eric; Gomez, Geena; Taylor, Richard H.; Toher, Cormac; Mehl, Michael J.; Levy, Ohad; Curtarolo, Stefano
Abstract : AFLOW‐SYM is a comprehensive crystal‐symmetry analysis suite catering to automated computational workflows and presenting a wealth of symmetry descriptions. This platform employs robust mapping techniques, validates calculated symmetry elements and resolves self‐consistent tolerances for each system to yield results more commensurate with experiments compared with other common symmetry packages. Abstract : Determination of the symmetry profile of structures is a persistent challenge in materials science. Results often vary amongst standard packages, hindering autonomous materials development by requiring continuous user attention and educated guesses. This article presents a robust procedure for evaluating the complete suite of symmetry properties, featuring various representations for the point, factor and space groups, site symmetries and Wyckoff positions. The protocol determines a system‐specific mapping tolerance that yields symmetry operations entirely commensurate with fundamental crystallographic principles. The self‐consistent tolerance characterizes the effective spatial resolution of the reported atomic positions. The approach is compared with the most used programs and is successfully validated against the space‐group information provided for over 54 000 entries in the Inorganic Crystal Structure Database (ICSD). Subsequently, a complete symmetry analysis is applied to all 1.7+ million entries of the AFLOW data repository. The AFLOW‐SYM package has been implemented in, and made available for, public use through the automated ab initio framework AFLOW .